Case Report: Successful treatment of steroid- and ruxolitinib-refractory gastrointestinal acute graft-versus-Host disease with anti-thymocyte globulin - Zhang, Lulu; Wu, Fan; Wang, Huiping; Zhai, Zhimin; Tao, Lili (Frontiers in Immunology, 2025)
Acute graft-versus-host disease (aGVHD), particularly with gastrointestinal (GI) involvement, remains a life-threatening complication after allogeneic hematopoietic stem cell transplantation (HSCT). Despite corticosteroids and ruxolitinib as first- and second-line therapies, up to 50% of patients develop refractory disease, with limited evidence guiding third-line interventions. Anti-thymocyte globulin (ATG), historically used in conditioning regimens, has shown variable efficacy in steroid-refractory aGVHD, but its role in patients previously exposed to ATG prophylaxis remains underexplored. Here, we report the case of a 19-year-old male with severe steroid- and ruxolitinib-refractory GI aGVHD, successfully treated with low-dose antithymocyte globulin (ATG) after failing multiple therapies (mycophenolate mofetil, anti-CD25 monoclonal antibody, mesenchymal stem cells, and methotrexate). This case underscores that, despite the prior use of ATG in the conditioning regimen and the multitude of available treatment options for refractory aGVHD, ATG can still be considered as a viable salvage therapy in situations where certain newer agents are not accessible.